Perkembangan Sistem Organ Platyhelmintes (Cacing Pipih) - Fela Rahmadiyanti; Fira Nur Fatimah; Luthfi Dhia Putri; Jodion Siburian; Afreni Hamidah; Desfaur Natalia (Jurnal Biogenerasi, 2026)
Platyhelminthes (flatworms) are simple triploblastic animals that represent an important stage in the evolution of organ systems. This article discusses the development, organization, and adaptation of organ systems in major classes of Platyhelminthes, including Turbellaria, Trematoda, and Cestoda. Using a literature review method, the study examines the morphology and physiology of flatworms based on scientific journals and biology references. The results show that although Platyhelminthes lack specialized circulatory and respiratory systems, they possess functional digestive, excretory, nervous, and reproductive systems. Their body organization reflects an early stage of organ system specialization in invertebrates, making them an important model for understanding animal evolution, adaptation, and biological complexity.